Effect of metal honeycomb structure on enhancing CHF in saturated downward-facing flow boiling. (March 2020) - Wang, Laishun; Yuan, Yuan; Erkan, Nejdet; Li, Fengchen; Okamoto, Koji
Highlights: The effect of hole diameter, pitch and hole diameter/pitch ratio of the metal porous honeycomb plate on flow boiling CHF was investigated. The reduction in boiling area has a big influence on downward-facing flow boiling CHF. Additional water supply through the metal porous media has significant CHF increase effect for some kinds of honeycomb plate. Abstract: There is a strong need to find a feasible approach to increase the Critical Heat Flux in downward-facing flow boiling effectively for the In-Vessel Retention strategy in advanced nuclear power plants. In this study, we designed metal porous honeycomb plates with different structures and used them in downward-facing flow boiling experiment to find a honeycomb plate that can enhance CHF in the downward-facing flow boiling to the largest extent and investigate the enhancement mechanism. The effect of the honeycomb structure and water supply through porous media on CHF are investigated. It is found that the reduction in boiling area has big effect on CHF and water supply through the porous media has significant effect on increasing CHF for some kinds of honeycomb structures.